2009
DOI: 10.2172/1048018
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Waste Forms for Electro-Chemical Salt Waste

Abstract: SUMMARYThis study was undertaken to examine alternative crystalline (ceramic/mineral) and glass waste forms for immobilizing spent salt from the Advanced Fuel Cycle Initiative (AFCI) electrochemical separations process (Echem). The AFCI is a program sponsored by U.S. Department of Energy (DOE) to develop and demonstrate a process for recycling used nuclear fuel (UNF). Echem is a molten salt process for the reprocessing of UNF in an electrorefiner and generates spent KCl-LiCl salt that is contaminated with alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…[1] Sodalite and cancrinite were identified as the overall best candidate mineral phases for incorporation of XCl 20 , because of their high concentrations of alkali and Cl, which, when combined, comprise 97 mole% of the waste. [1] The FY2009 scoping studies showed that sodalite can be easily synthesized by the sol-gel process. However, it is produced in the form of a fine powder with particle sizes on the order of a few microns.…”
Section: Tablesmentioning
confidence: 99%
See 3 more Smart Citations
“…[1] Sodalite and cancrinite were identified as the overall best candidate mineral phases for incorporation of XCl 20 , because of their high concentrations of alkali and Cl, which, when combined, comprise 97 mole% of the waste. [1] The FY2009 scoping studies showed that sodalite can be easily synthesized by the sol-gel process. However, it is produced in the form of a fine powder with particle sizes on the order of a few microns.…”
Section: Tablesmentioning
confidence: 99%
“…10 ] used in FY2009 is presented elsewhere. [1] ) XCl 10 -loadings of 5-30 mass% were prepared with TeO 2 as the main glass former in a desired ratio, and modifiers (B 2 O 3 , Li 2 O, and Na 2 O) were added separately to improve glass processability. The batches were then placed in Pt/5%Au crucibles with Pt/10%Rh lids to reduce the volatility of chlorides during melting and then melted for ~25 minutes at 600-800°C to verify an optimum melting temperature for the tellurite glasses.…”
Section: Tablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other alternative options to sodalite are currently under consideration, including alternative naturally occurring minerals that contain the waste components . The work presented here includes a brief overview of the candidate minerals, the methods used to produce some of them, and results from the characterization of the mineral properties.…”
Section: Introductionmentioning
confidence: 99%